The Effect of Contextual Teaching and Learning (CTL) Model on Reaction Rate Material on Critical Thinking Ability and Character of Student - Arwin, Muh.; Pikoli, Masrid; Sihaloho, Mangara; Kunusa, Wiwin Rewini; Tangio, Julhim S.; Munandar, Haris (Universitas Negeri Gorontalo, 2025)
This research investigates the impact of the Contextual Teaching and Learning (CTL) model on critical thinking abilities and student character in the reaction rate topic at SMA Negeri 3 Gorontalo Utara. This research employs a quantitative methodology with a near-experimental design, specifically employing a one-group pre-test and post-test design. Data were gathered through questionnaires and tests. The study's population consisted of grade XI students at SMA Negeri 3 Gorontalo Utara throughout the opening term of the academic cycle for 2024-2025. A total sampling method was used, selecting 50 students from two classes who enrolled in chemistry specialization. The findings indicate that the application of the CTL model led to an improvement in critical thinking skills, with the experimental class showing a mean pre-test result of 37.56% and a post-test result of 84.22%, whereas the replication group recorded pre-test and post-test averages of 37.33% and 83.89%, respectively. As for character growth, the experimental group displayed an average score of 80.13%, while the replication group showed 79.90%. Both classes demonstrated significant progress, as shown by the consistency of the results in both groups. The outcomes of the paired sample t-test reveal a noteworthy value of 0.000 < 0.05, prompting the dismissal of H0 and the endorsement of Ha, confirming that the CTL model positively affects critical thinking skills and student character in reaction rate material.